A spirit of trust a reading of Hegel's Phenomenology - Brandom, Robert (The Belknap Press of Harvard University Press, 2019)
This book presents a completely new retelling, in contemporary terms, of the romantic rationalist adventure of ideas that is Hegel's classic Phenomenology of Spirit. At its core is a nonpsychological conception of the conceptual, according to which the fact that there are laws of nature means that the objective world, no less than our thought about it, is already in conceptual shape. What Hegel takes to be the single biggest thing that ever happened in human history--the shift from traditional to distinctively modern ways of living, acting, and thinking--is explained as a fundamental change in the structure of normativity. Properly understanding that progressive structural transformation in turn points the way to a more perfect form of self-conscious life, and so to post-modernity as a dawning third age of what he calls "Spirit." What emerges is an account of what we most deeply are, in the form of a sweeping "history of the progress of the consciousness of freedom."--